THE RELATIONSHIP BETWEEN BLOOD GLUCOSE LEVELS AND VISUAL ACUITY IN DIABETES MELLITUS PATIENTS IN TOTO KABILA REGIONAL HOSPITAL - Novita Angraeni; Nasrun Pakaya; Sitti Fatimah Meylandari Arsad (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Diabetes Mellitus (DM) is a chronic disease caused by a lack of insulin production by the pancreas or the insulin produced cannot be used effectively by the body . This causes the formation of microaneurysms in the retinal blood vessels which make the blood vessels fragile and easily ruptured, causing visual impairment in the form of decreased visual acuity. The general objective of this study was to determine the relationship between blood glucose levels and visual acuity in patients with diabetes mellitus at Toto Kabila Hospital. This research uses a quantitative research type with a research design. descriptive analytical using cross sectional approach method . The population in this study were DM patients who visited the Eye Polyclinic at Toto Kabila Hospital and the sample in this study used the technique accidental sampling with a total of 87 samples. The instrument in this study used an observation sheet. The data analysis technique used the chi-square test . obtained value pvalue = 0.00 0 which means there is a relationship between blood glucose levels and visual acuity in diabetes mellitus patients at Toto Kabila Regional Hospital .